Nature versus intensity of intoxication: Co-ingestion of alcohol and energy drinks and the effect on objective and subjective intoxication. (1st November 2017) - Forward, Jessica; Akhurst, Jane; Bruno, Raimondo; Leong, Xiao; VanderNiet, Amelia; Bromfield, Holly; Erny, Jacqueline; Bellamy, Tessa; Peacock, Amy
Highlights: Three studies examined objective/subjective intoxication from alcohol and energy drinks (AmED). Within-subject, placebo-controlled, double-blind study design with real-world doses. AmED consumption predicted lower objective intoxication levels than alcohol-only. AmED reduced ratings of intoxication, with no change in stimulation and sedation. The sugar content of energy drinks is likely the primary driver of noted effects. Abstract: Background: We report a series of studies examining the effect of alcohol mixed with energy drinks (AmEDs) versus alcohol on objective intoxication (breath alcohol concentration; BrAC), intensity, and nature of intoxication. We also aimed to disentangle the role of energy drink (ED) ingredients in any effects. Method: Three within-subject double-blind placebo-controlled studies measured BrAC, subjective intoxication and impairment ('intensity of intoxication'), stimulation and sedation ('nature of intoxication') following administration of ED, Cola, Caffeine + Sugar, and Placebo with alcohol (Study 1, n = 18); ED, Caffeine-only, Sugar-only and Placebo with alcohol (Study 2, n = 20); and ED and Placebo with alcohol (Study 3, n = 27). Results: Significant moderate-to-large magnitude BrAC decrements and delayed time to peak BrAC were observed after ED administration versus Placebo. However, no meaningful BrAC differences between ED and other active conditions were observed in Study 1 and 2. After BrAC adjustment, moderate-to-large magnitude reductions in intoxication and impairment ratings were observed after ED versus Placebo on the ascending limb in all studies and at peak in Study 2 and 3. No meaningful differences were observed in intoxication and impairment ratings between ED and Caffeine + Sugar and Cola conditions (Study 1); ratings were lower after ED versus Sugar-only (Study 2). Stimulation and sedation ratings did not differ between ED and Placebo. Conclusion: Reductions in objective intoxication and perceived intensity of intoxication, but not nature of intoxication, were observed after AmED consumption. However, effects may be common to alcohol mixers containing sugars (objective intoxication) and caffeine (intensity of intoxication) and specific to a laboratory setting.